Rotary inverted pendulum with magnetically external perturbations as a source of the pendulum’s base navigation commands - Pujol-Vazquez, Gisela; Acho, Leonardo; Mobayen, Saleh; Nápoles, Amelia; Pérez, Vega (Journal of the Franklin Institute, 2018)
The main objective of this paper is to drive a rotary inverted pendulum by following a desired navigation instruction. This navigation is commanded by the user through a new electromagnetic device which is allowed to perturb the pendulum from its upright position. This apparatus consists of an electronic magnetic driving circuit to introduce commands and realized via two operated magnetic coils. So, the external programmed magnetic perturbation can be seen as external commandments. Therefore, the control problem statement is solved via a modified regulation control implementation, to maintain the pendulum on its upright position and giving free manipulation of the base of the rotary inverted pendulum. Hence, by using the corresponding H∞-linear matrix inequality technique, a static state controller is designed and tested experimentally so supporting our findings.